IoT System with ESP32 for Smart Drip Irrigation and Climate Monitoring in Greenhouses - Joseph J. Correa-Quiroz; Max A. Toribio-Barrueto; Cristian Castro-Vargas (Emerging Science Journal)
The depletion of water resources and the need for sustainable agricultural practices require innovative technological solutions. This study develops an IoT-based smart drip irrigation and climate monitoring system for greenhouses using the ESP32 microcontroller. The methodology implements DHT11 sensors for temperature and humidity, GUVA-S12SD for UV radiation, capacitive soil moisture sensors, and HC-SR04 for water level measurement. Real-time data is displayed on an LCD screen and transmitted to the Arduino Cloud, enabling remote monitoring and control. Field tests showed a 35% reduction in water consumption compared to traditional methods, improving crop environmental conditions and reducing operating costs. The system operates in automatic and manual modes, adapting to various climatic conditions and user needs. The main innovation lies in its optimized water use efficiency through smart drip irrigation, ensuring precise humidity control and minimizing waste. Furthermore, its scalability allows integration with renewable energy sources, increasing its autonomy and sustainability. This approach fosters climate-resilient agriculture, aligned with the Sustainable Development Goals (SDGs), by promoting water conservation and efficient resource use.